The Position and Juridical Implications of Ex Gratia Payments in Insurance Claim Settlements from the Perspective of Civil Law - Teuku R. Muhammad Rajih; Yusri Yusri; Ria Fitri (International Journal of Law and Society, 2026)
The practice of Ex Gratia payments in insurance has developed as a discretionary policy to maintain good relations with insured parties, protect corporate reputation, and facilitate dispute resolution without prolonged litigation. However, the absence of explicit regulation under Indonesian law creates legal uncertainty regarding the legal status of Ex Gratia payments, their implications for the rights and obligations of the parties, and the legal certainty following such payments. This study aims to examine the juridical construction of Ex Gratia payments as a civil legal act outside contractual obligations and to analyze their legal implications within insurance agreements. This research employs a normative legal method using statutory, conceptual, and analytical approaches. The study relies on secondary data consisting of primary, secondary, and tertiary legal materials collected through library research. Data were analyzed qualitatively using descriptive-analytical and prescriptive methods. The findings indicate that Ex Gratia payments do not arise from contractual obligations under an insurance policy but constitute voluntary civil legal acts based on moral, humanitarian, reputational, or business considerations. Nevertheless, such payments may establish new legal relationships if expressly stipulated in a binding agreement or written commitment. Furthermore, Ex Gratia payments may affect the insured’s right to sue, the waiver of rights, the principle of subrogation, and the balance of legal rights and obligations between the parties, highlighting the need for clearer legal regulation to ensure certainty and consistency in insurance practice.